Selective aerobic oxidation of furfural to maleic anhydride with heterogeneous Mo–V–O catalysts. Issue 10 (25th April 2016) - Li, Xiukai; Ho, Ben; Zhang, Yugen
Abstract : A binary Mo–V metal oxide catalyzed the selective aerobic oxidation of furfural to maleic anhydride (MA) with up to 65% yield. Abstract : A heterogeneous catalytic system using binary Mo–V metal oxides as catalysts was demonstrated for the selective aerobic oxidation of furfural to maleic anhydride (MA). Aspects such as the solvent for the reaction, the phase composition and the Mo/V ratio for the catalyst, and other reaction conditions were investigated in detail. Up to 65% yield of MA was achieved over the Mo4 VO14 catalyst in an acetic acid solvent under optimal conditions. The catalyst could be recycled. The reaction mechanism and the role of the acetic acid solvent were also discussed.